2016
DOI: 10.1016/j.bbmt.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Care Patterns Associated with Pediatric Palliative Care among Children Who Underwent Hematopoietic Stem Cell Transplant

Abstract: Background Stem cell transplantation (SCT) is an intensive therapy offering the possibility of cure for life-threatening conditions although with risk of serious complications and death. Outcomes associated with pediatric palliative care (PPC) for children who undergo SCT are unknown. Objective To evaluate whether PPC consultation is associated with differences in end-of-life (EOL) care patterns for children who underwent SCT and did not survive Methods Medical records of children who underwent SCT at Bost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(105 citation statements)
references
References 39 publications
2
102
0
1
Order By: Relevance
“…(1821) Recent studies, using parent report after patient death, have shown that pediatric patients who undergo HCT are more likely to “suffer highly” from their last therapy and die in the ICU, with less opportunity for EOL care planning. (20, 21) Additionally, pediatric oncology patients who underwent HCT had a shorter time interval between completion of a do not resuscitate (DNR) order and death, were enrolled less often in hospice, and were less likely to die at home as compared to pediatric oncology patients who did not undergo HCT as a part of their treatment. (22)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1821) Recent studies, using parent report after patient death, have shown that pediatric patients who undergo HCT are more likely to “suffer highly” from their last therapy and die in the ICU, with less opportunity for EOL care planning. (20, 21) Additionally, pediatric oncology patients who underwent HCT had a shorter time interval between completion of a do not resuscitate (DNR) order and death, were enrolled less often in hospice, and were less likely to die at home as compared to pediatric oncology patients who did not undergo HCT as a part of their treatment. (22)…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we explored differences in EOL features of AYA HCT patients based on their cause of death, regardless of location of death. This descriptive study builds upon very limited literature characterizing the demographic and EOL characteristics of AYA patients who have undergone allogeneic HCT,(20, 22) and to our knowledge it is the first study to assess the physical and psychological symptoms of this uniquely vulnerable patient population during the last month of life.…”
Section: Introductionmentioning
confidence: 99%
“…86 Finally, among children receiving HCT at a third centre, 97% of families who received specialty PPC discussed the prognosis of the child compared with 83% of families who did not receive PPC. 87 These discussions occurred earlier with PPC than without PPC (8 days vs 2 days before the death of the child), and children were less likely to receive intense end-of-life interventions such as intubation or cardiopulmonary resuscitation.…”
Section: Current Era Of Ppc Oncology Research (2010 To Present)mentioning
confidence: 99%
“…Investigators of three studies 8587 considered specialty PPC as a separate intervention, and compared children’s end-of-life experiences with or without it. First, among 114 children who died at a children’s hospital (not all from cancer), inpatient PPC consultation was associated with higher frequencies of pain assessment and management, increased use of integrative medicine, fewer diagnostic or invasive procedures in the last 48 h of life, and more orders to limit resuscitation than those who did not receive inpatient PPC consultation.…”
Section: Current Era Of Ppc Oncology Research (2010 To Present)mentioning
confidence: 99%
“…2224 However, results from several studies suggest that early palliative care consultations improve the detection of untreated symptoms, enhance communication and documentation of advance care planning, and increase the likelihood of hospice enrollment and avoidance of in-hospital deaths. 2529 …”
Section: Aca Impact On End-of-life Carementioning
confidence: 99%